Chronic spearfishing may indirectly affect reef health through reductions in parrotfish bite rates - Christina Skinner; Steven P. Newman; Stephen Box; Andrzej Narozanski; Nicholas V. C. Polunin (Journal of Fish Biology, 2019)
The grazing behaviour of two Caribbean parrotfish, a fished species, the stoplight parrotfish Sparisoma viride and a non‐fished species, the striped parrotfish Scarus iseri , were studied in the presence (fished site) and absence (marine reserve) of chronic spearfishing activity. Diurnal feeding periodicity did not differ between the sites in either species: roving individuals had significantly higher bite rates in the afternoon, while territorial individuals foraged consistently throughout the day. Mean bite rate varied between sites in both species. Abundance, biomass and bite rates of S. viride were all significantly higher within the reserve, except for roving S. viride which had a higher mean bite rate in the afternoon outside the reserve compared with within it, attributable to maximisation of feeding in the afternoon when fishing risk was lower. Scarus iseri mean abundance and bite rate were greater outside the reserve, potentially because reduction in large territorial herbivores allowed S. iseri to feed more rapidly. By reducing the grazing potential of the remaining S. viride individuals the effect of fishing is greater than would be predicted from biomass changes alone. Less grazing by S. viride would not be compensated for by the increase in grazing by S. iseri because the latter feeds on different algae. Spearfishing of key parrotfish species reduces grazing potential directly by extraction and indirectly by changing behaviour.